Posted by **Jonnie** on Thursday, April 2, 2009 at 11:18pm.

Solve by the subsitution method.

2x+4y=-6

-3x+y=23

y=23+3x

2x +4(23+3x)=-6

2x +92 +12 x =-6

x=7

y= 23 I am lost after this could some one help me

## Answer This Question

## Related Questions

- algebra - I have tried these problem cannot get the answer so could some one ...
- subsitution method - Can some one show me how to use the Substitution method to ...
- algebra - solve using the subsitution method 4x+4y=36 4x+4y=12 If the system has...
- algebra - whats the subsitution method for: 7x+63y=12 x=3-9y
- Subsitution Method Grrr - Please show me the steps and solve. 3x+5y=1025 x+5=275
- Algebra - Solve by elimination method. 7r-3s=14 3r+7s=64 Could never figure out ...
- algebra - solve by subsitution 2x+y=9 8x+4y=36
- maths - the easiest method for simutanious equations using subsitution method is...
- algebra - solve by subsitution 6x + 5y = 27 x = 17 -8y my answer was (3,-7)
- Algebra - How do I solve for the elimination method: 5x + 3y= -7 and 7x - 2y =13...

More Related Questions